Using the multi-omics approach to reveal the silk composition in Plectrocnemia conspersa - Rouhová, Lenka; Sehadová, Hana; Pauchová, Lucie; Hradilová, Miluše; Žurovcová, Martina; Šerý, Michal; Rindoš, Michal; Žurovec, Michal (Frontiers in Molecular Biosciences, 2022)
Similar to Lepidoptera, the larvae of Trichoptera are also capable of producing silk. Plectrocnemia conspersa, a predatory species belonging to the suborder Annulipalpia, builds massive silken retreats with preycapturing nets. In this study, we describe the silk glands of P. conspersa and use the multi-omics methods to obtain a complete picture of the fiber composition. A combination of silk gland-specific transcriptome and proteomic analyses of the spun-out fibers yielded 27 significant candidates whose full-length sequences and gene structures were retrieved from the publicly available genome database. About one-third of the candidates were completely novel proteins for which there are no described homologs, including a group of five pseudofibroins, proteins with a composition similar to fibroin heavy chain. The rest were homologs of lepidopteran silk proteins, although some had a larger number of paralogs. On the other hand, P. conspersa fibers lacked some proteins that are regular components in moth silk. In summary, the multi-omics approach provides an opportunity to compare the overall composition of silk with other insect species. A sufficient number of such studies will make it possible to distinguish between the basic components of all silks and the proteins that represent the adaptation of the fibers for specific purposes or environments.